Respostas
respondido por:
46
3(x-1)-2(x+4)=10
3x - 3 - 2x - 8 = 10
3x - 2x = 10 + 3 + 8
x = 21
3x - 3 - 2x - 8 = 10
3x - 2x = 10 + 3 + 8
x = 21
anamagalaes:
Obrigado
respondido por:
14
3 ( x - 1 ) - 2 ( x + 4 ) = 10
3x - 3 - 2x - 8 = 10
3x - 2x = 10 + 8 + 3
1x = 21
x = 21 / 1
x = 21
Espero ter ajudado e bons estudos!!!
3x - 3 - 2x - 8 = 10
3x - 2x = 10 + 8 + 3
1x = 21
x = 21 / 1
x = 21
Espero ter ajudado e bons estudos!!!
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás